Blockchain Applications in Fisheries - Asha Vijay T.; Raju M.S. (E3S Web of Conferences, 2023)
Urbanization has led to increasing fish consumption, resulting in high demand for fish and fish products. Challenges in this sector, include fraudulent fish supply, overfishing, unscientific handling, quality concerns, etc. Blockchain-based systems in the seafood sector could provide traceability access to the seafood for the consumers and authorities to know if the seafood consumed/sold is legal, ethical, hygienic, economic, etc. Blockchain platforms like Ethereum promote secure digital collaboration of the actors across the supply chain eliminating the intermediaries. The literature documents a very limited number of blockchains that operate in the fisheries sector. Pacifical Atato is designed to promote and develop yellowfin tuna supply chains of Pacific island nations. Project Provenance Limited seeks to bring an end to the unsustainable fishing practices. Tuna distribution through transparent, novel chains is the goal of TraSeable solutions. Treum explored the investments to develop the supply chains of fisheries in the South Pacific. IBM’s Food Trust traces food supplies, including farmed shrimp from India, and is affiliated with retailers like Walmart, Nestle, etc. OpenSC is a World Wildlife Fund (WWF) project that ensures ethical product sourcing and uses QR (Quick Response) code scanning and RFID (Radio Frequency Technology) to track fish.